Investigation of the thermal properties of [Cd(hydet-en)2Pd(CN)4] and [Zn(hydet-en)2Pd(CN)4] single crystals - Yakuphanoğlu, Fahrettin; Karadag, A.; Sekerci, M. (Springer, 2006)
Thermal properties of the single crystals have been investigated by thermogravimetry (TG) and differential scanning calorimetry (DSC) techniques. The thermodynamic parameters such as activation energy and enthalpy and thermal stability temperature of the samples were calculated from the differential thermal analysis (DTA) and TG data. The activation energies for first peak of DTA curves were found as 496.65 (for Cd-Pd) and 419.37 kJ mol(-1) (for Zn-Pd). For second peak, activation energies were calculated 116.56 (for Cd-Pd) and 173.96 kJ mol(-1) (for Zn-Pd). The thermal stability temperature values of the Cd-Pd and Zn-Pd compounds at 10 degrees C min(-1) heating rate are determined as approximately 220.7 and 203 degrees C, respectively. The TG results suggest that thermal stability of the Cd-Pd complex is higher than that of the Zn-Pd complex.
15th Annual Workshop and Exhibition of the Canadian-Thermal-Analysis-Society -- MAY 17-18, 2005 -- Boucheville, CANADA
Keywords: kinetics parameters; single crystal; thermal analysis